ABOUT THE SPACE DISTRIBUTION OF STARS IN THE SELECTED SKY FIELDS - Dragunova, A. V.; Yasinskaya, M. P. (Одеські астрономічні публікації, 2017)
By the results of a photometry of stars in six Captain Areas, located near to a galactic plane, the densities of absorbing matter and space distribution of stars in these sky fields are determined. The comparison of maximal concentration of stars of various spectral classes to an arrangement of the interstellar dust clouds is carried out.